The Involvement of Nitric Oxide and Endothelin-1 in Exercise-Induced Bronchospasm in Young Soccer Players - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Objective: To investigate the levels of nitric oxide (NO) and endothelin-1 (ET-1) in soccer players with exercise-induced bronchospasm (EIB), to test whether these endogenous vasoactive molecules are involved in the development of EIB, and to examine the possible participation of reactive oxygen metabolites in these alterations. Design: Observational study. Setting: Football club. Participants: Forty-three soccer players (N = 43) aged 16 to 22 years performed maximal exercise test on a treadmill by using the Bruce protocol. Interventions: Respiratory function tests were evaluated before and after exercise tests. Participants were grouped as control (n = 35) or EIB (n = 8) groups according to the respiratory function test results. Main Outcome Measures: Endothelin-1, NO, carbonyl, malondialdehyde, and glutathione levels were determined from the blood samples taken before and after exercise tests. Results: In the control group, significant decreases in plasma ET-1 and serum NO levels were determined after exercise. On the other hand, plasma malondialdehyde and carbonyl levels were significantly decreased, whereas glutathione levels were significantly increased after exercise. In the EIB group, blood levels of NO, ET-1, carbonyl, and malondialdehyde after exercise were found to be significantly increased compared with pre-exercise levels. Conclusions: These findings demonstrate that in young soccer players, EIB is associated with elevated serum NO and plasma ET-1 levels. Moreover, significant increases in lipid peroxidation and protein oxidation and decreases in antioxidant sulfhydryl (RSH) content indicate a significant compromise in the blood antioxidant status and the presence of systemic oxidative stress in young athletes with EIB.
Keywords: exercise-induced bronchospasm; nitric oxide; endothelin-1; INDUCED BRONCHOCONSTRICTION; AIRWAY INFLAMMATION; BRONCHIAL HYPERRESPONSIVENESS; GLUTATHIONE; CHILDREN; INCREASE; ASTHMA; TISSUE; OXYGEN